2013
DOI: 10.1038/srep02049
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Somatotopic Representations of Chinese Action Verbs in the Motor and Premotor Cortex

Abstract: The embodied view of language processing holds that language comprehension involves the recruitment of sensorimotor information, as evidenced by the somatotopic representation of action verbs in the motor system. However, this review has not yet been examined in logographic scripts such as Chinese, in which action verbs can provide explicit linguistic cues to the effectors (arm, leg, mouth) that conduct the action (hit, jump, drink). We compared the somatotopic representation of Chinese verbs that contain such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 88 publications
(142 reference statements)
0
11
0
Order By: Relevance
“…Some authors have reported enhanced activity within the premotor cortex 71 , 72 , which could endow individuals with information needed to prepare upcoming actions. Other studies have identified more extensive activity involving also the primary motor cortex 61 , 65 , 66 , 68 , 73 , suggesting that MR can extend further towards the nervous system’s motor pathways and closer to the musculature responsible for movement execution.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some authors have reported enhanced activity within the premotor cortex 71 , 72 , which could endow individuals with information needed to prepare upcoming actions. Other studies have identified more extensive activity involving also the primary motor cortex 61 , 65 , 66 , 68 , 73 , suggesting that MR can extend further towards the nervous system’s motor pathways and closer to the musculature responsible for movement execution.…”
Section: Introductionmentioning
confidence: 95%
“…However, MR is known to occur during the perception of action semantics in language. Brain imaging experiments have found increased activity in the motor regions elicited by words describing action execution 64 68 . This is to say that action-related semantics in language can induce a somatotopically fine-grained MR 69 , 70 .…”
Section: Introductionmentioning
confidence: 99%
“…Subject words and verbs showed stronger activation than control stimuli (checkerboard) in the word reading stage ( ps  < .05), and the control condition had less activation than the other three word conditions ( ps  < .05) in the imitation stage. The language enhancement effect on both the word reading and imitation stages in the left precentral gyrus may have been due to that the semantic processing of hand action‐related words automatically activates the hand action area (Hauk et al., 2004; Postle, McMahon, Ashton, Meredith, & de Zubicaray, 2008; Pulvermüller, 2005; Wu et al., 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Subject words and verbs showed stronger activation than control stimuli (checkerboard) in the word reading stage (ps < .05), and the control condition had less activation than the other three word conditions (ps < .05) in the imitation stage. The language enhancement effect on both the word reading and imitation stages in the left precentral gyrus may have been due to that the semantic processing of hand action-related words automatically activates the hand action area(Hauk et al, 2004;Postle, McMahon, Ashton, Meredith, & de Zubicaray, 2008;Pulvermüller, 2005;Wu et al, 2013).In the left IPL (−50, −59, 43), right postcentral gyrus (PostG) (47, −22, 48) and right IFG (50, 16, 10), the significant main effect of word type in the imitation stage (IPL: F 3,54 = 6.133, p < .01; PostG: F 3,54 = 11.361, p < .01; IFG: F 3,54 = 6.278, p < .01) indicated that the object word condition (IPL: M = 0.08, SE = 0.22; PostG: M = 0.15, SE = 0.12; IFG: M = 0.39, SE = 0.16) had a stronger signal change than the subject word (IPL: M = −0.78, SE = 0.19; PostG: M = −0.33, SE = 0.12; IFG: M = 0.02, SE = 0.14) and control condition (IPL: M = −0.76, SE = 0.22, ps < .05; PostG: M = −0.34, SE = 0.14, ps < .001;…”
mentioning
confidence: 99%
“…Furthermore, Wu et al . (), showed that this somatotopic organization of action concept representation concerns the common way agents use and understand action categories in different languages and cultures. In this experiment, processing Chinese action verbs elicited similar somatotopic representations in the motor and premotor cortex as already established for alphabetic scripts.…”
Section: How Intentions and Motor Representations Interlock: The Sensmentioning
confidence: 91%